2011
DOI: 10.1080/10640266.2011.564976
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Disordered Eating Attitudes Among Male and Female Young Talented Dancers: Findings From the UK Centres for Advanced Training

Abstract: Correlates of disordered eating attitudes were examined with a mixed-sex sample of 347 young talented dancers aged 10-18 years from all UK Centres for Advanced Training. Equal proportions of females (7.3%) and males (7.6%) were symptomatic for disordered eating but correlates differed: for females, self-evaluative perfectionism, waking up > twice/night and hours of non-dance physical activity were predictive while for males, only the combination of self-evaluative and conscientious perfectionism was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
3
28
1
2
Order By: Relevance
“…The current findings demonstrated that high standards and self-criticism are positively associated with eating restraint, eating concern, weight concern and shape concern, with self-criticism demonstrating relatively stronger associations with the measured aspects of eating psychopathology than did high standards. This closer relationship of eating psychopathology with self-criticism rather than with high standards supports previous research examining perfectionism and eating psychopathology in a heterogeneous sample of dancers (Nordin-Bates et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The current findings demonstrated that high standards and self-criticism are positively associated with eating restraint, eating concern, weight concern and shape concern, with self-criticism demonstrating relatively stronger associations with the measured aspects of eating psychopathology than did high standards. This closer relationship of eating psychopathology with self-criticism rather than with high standards supports previous research examining perfectionism and eating psychopathology in a heterogeneous sample of dancers (Nordin-Bates et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…The present study investigated the interactive effects of high standards and self-criticism on eating psychopathology among university-aged dancers. The current sample's levels of perfectionism were higher than a previous study of female dancers (Nordin-Bates et al, 2011), which also had a relatively heterogeneous sample of dancers in terms of dance styles and hours of weekly dance activity. Nordin-Bates et al had recruited from a younger sample than the current sample, and it had comprised a relatively committed group of dancers, so it is unclear why their levels of perfectionism were slightly lower than the current sample of university-aged dancers.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The existence of specific personality traits along with sociocultural influences may explain, to some extent, the high prevalence of ED among high-risk occupations (9). Some authors have mentioned that perfectionism and low selfesteem, usually found among dancers, might explain why ED appear to be more prevalent among this group of people (9,10). Nevertheless, this statement remains controversial taking into account the disparity of results, probably due to methodological differences among studies (7).…”
Section: Introductionmentioning
confidence: 84%